PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PPKn UNIVERSITAS RIAU - Afillda Rappiana Lubis; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by online learning and student learning outcomes of the Riau University PPKn study program. The formulation of the problem in this study is how the effect of online learning and student learning outcomes of the Riau University PPKn study program. The research objective was to determine how the effect of online learning and student learning outcomes of the Riau University PPKn study program. The benefits of this research are theoretical benefits, namely this research is expected to contribute in the field of education, especially those related to writing scientific papers. The practical benefit is as a basis and reference for further research related to online learning and student learning outcomes on campus to become material for further study. The population in this study were students of class 2017, 2018, and 2019, Riau University PPKn Study Program, totaling 215 students. The sample in this study were 68 students of the Riau University PPKn Study Program, which were determined by random sampling technique. The data collection instruments were questionnaires, documentation, and interviews. Processing data with quantitative descriptive analysis using simple linear regression formula assisted by SPSS version 16 application by stating hypotheses; there is an influence between online learning on student learning outcomes of the Riau University PPKn Study Program. Based on the results of research on the effect of online learning on student learning outcomes of the Riau University PPKn Study Program, there is a significant influence between the effect of online learning on student learning outcomes of the Riau University PPKn Study Program by 27.5%.Key Words: Influence, Online Learning, Student Learning Outcomes